Translating Figurative Images of Il Fu Mattia Pascal - Papa, Mirela (Richtmann Publishing, 2012)
The metaphor is one of the most productive and traditional figure of speech in standard language. Newmark stresses thatmetaphor responds to a double objective: referential and cognitive objective, that consists in the description of a concept, a person, onobject or an action, as clearly as possible, and the pragmatic or aesthetic objective, that aims to stimulate the senses, to attract attentionor to cause surprise. These aims are usually connected to each other, but sometimes one becomes more important than another inaccording to the type of the text and its contextual function. Writers use this figure of speech in their works to help the reader have adeeper understanding of the character or of a situation, as far as the emotional as well as the physical features is concerned. In thisspeech, we will make an analysis of the metaphors used by the Italian writer Luigi Pirandello in his work Il Fu Mattia Pascal and we willanalyze the problems it presents when translated in Albanian. We will notice the difficulties that the translators have encountered totransmit this figure of speech in the target language and the ways they have used to solve these difficulties.